Secondary battery electrode binder
The challenges of battery electrode adhesion and manufacturing process are solved by using VDF-based polymers optimized with intrinsic viscosity and end-group structures, achieving efficient electrode fabrication and excellent electrochemical properties.
Patent Information
- Application Number
- CN202380073583.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2023-10-11
- Publication Date
- 2025-05-30
AI Technical Summary
In the battery field, especially in sodium or lithium batteries, there is a challenge to provide electrode adhesives characterized by very good adhesion, while not negatively affecting the electrode manufacturing process, such as increasing slurry viscosity affecting electrode production.
Using a VDF-based polymer, consisting of repeat units derived from VDF and optional fluorinated comonomers, the intrinsic viscosity ranges from 0.25 l/g to 0.60 l/g, and contains a specific end group structure to improve adhesion and reduce slurry viscosity.
An electrode forming composition with improved slurry viscosity at low shear rates is achieved, providing good adhesion to metal substrates, simplifying the electrode manufacturing process, and improving the performance of the electrodes.
Smart Images

Figure BDA0005363101730000131 
Figure BDA0005363101730000161 
Figure BDA0005363101730000171
Abstract
Description
[0001] Cross - reference to prior applications
[0002] This application claims priority to European Application No. 22202255.0 filed on October 18, 2022 and European Application No. 23157209.0 filed on February 17, 2023, the entire contents of which are incorporated herein by reference for all purposes. Technical field
[0003] The present invention relates to vinylidene fluoride polymers used as binders for electrodes in secondary batteries. Background art
[0004] It is known in the art that fluoropolymers are suitable as binders for manufacturing electrodes for use in electrochemical devices such as secondary batteries.
[0005] Generally, it is known to increase the molecular weight of fluoropolymers to improve the properties of articles made from these materials, particularly in terms of mechanical properties and the adhesion of the electrode to the current collector.
[0006] However, increasing the molecular weight of the fluoropolymer will increase the viscosity of the electrode - forming formulation (also known as the electrode paste) containing it, making the processing and coating processes in electrode manufacturing more difficult.
[0007] CN110183562 discloses the preparation of high - molecular - weight PVDF by using diisopropyl peroxydicarbonate as an initiator. The resulting PVDF is characterized by high crystallinity, which makes the electrode paste composition containing this PVDF unable to be used for preparing electrodes. Therefore, high - crystallinity PVDF is blended with a VDF - based copolymer to obtain a polymer mixture suitable for use as an electrode binder.
[0008] In the technical field of batteries, especially sodium or lithium batteries, there is a problem of providing an electrode binder characterized by very good adhesion while not having a negative impact on the electrode manufacturing process, such as negatively affecting electrode production due to an increase in paste viscosity. Summary of the invention
[0009] It has been found that certain vinylidene fluoride polymers are endowed with very good adhesion to metal substrates and can be used to prepare electrode - forming compositions having improved paste viscosity at low shear rates.
[0010] Accordingly, an object of the present invention is a polymer [polymer (F)] based on VDF, which consists of repeating units derived from VDF and optionally repeating units derived from at least one fluorinated comonomer (CF) different from VDF, and the polymer (F) has an intrinsic viscosity measured in dimethylformamide at 25 °C in the range of 0.25 l / g to 0.60 l / g, more preferably 0.30 l / g to 0.50 l / g.
[0011] wherein the polymer (F) is characterized by containing end groups having the formula (I):
[0012] –(R a ) x -O-CO-O-CH 2 -CH 3 (I)
[0013] wherein R a is a C 1 -C 5 linear or branched hydrocarbon group, and x is an integer selected from 1 and 0, and
[0014] the end groups having the formula (I) are present in an amount of at least 0.2 / 10,000 VDF units, preferably at least 1.0 / 10,000 VDF units, and at most 10 / 10,000 VDF units.
[0015] A second object of the present invention relates to an electrode-forming composition (C), which comprises:
[0016] a) at least one electrode active material (AM);
[0017] b) at least one binder (B), wherein the binder (B) comprises at least one polymer (F) as defined above; and
[0018] c) at least one solvent (S).
[0019] In another object, the present invention relates to the use of the electrode-forming composition (C) in a method for manufacturing an electrode [electrode (E)], the method comprising:
[0020] (I) providing a metal substrate having at least one surface;
[0021] (II) providing the electrode-forming composition (C) as defined above;
[0022] (III) applying the composition (C) provided in step (II) to the at least one surface of the metal substrate provided in step (I), thereby providing an assembly comprising a metal substrate having the composition (C) coated on the at least one surface;
[0023] (IV) Dry the components provided in step (III);
[0024] (V) Subject the dried components obtained in step (IV) to a compression step to obtain the electrode (E) of the present invention.
[0025] In a further object, the present invention relates to an electrode (E) obtainable by the method of the present invention.
[0026] In yet a further object, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention. Detailed Description
[0027] The term "VDF-based polymer" is intended to mean a VDF homopolymer (PVDF) and a VDF-based copolymer comprising repeating units derived from VDF and repeating units derived from at least one fluorinated comonomer (CF) different from VDF.
[0028] The VDF-based polymer (F) of the present invention does not contain any hydrogenated monomers bearing polar groups.
[0029] The term "repeating unit derived from vinylidene fluoride (usually also denoted as vinylidene difluoride, 1,1-difluoroethylene, VDF)" is intended to mean a repeating unit having the formula CF 2 =CH 2 .
[0030] Non-limiting examples of suitable fluorinated comonomers (CF) include in particular the following:
[0031] (a) C 2 -C 8 fluoroolefins and / or perfluoroolefins such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene, hexafluoroisobutene, fluoroethylene; 1,2-difluoroethylene and trifluoroethylene;
[0032] (b) perfluoroalkyl vinylenes having the formula CH 2 =CH-R f0 wherein R f0 is a C 1 -C 6 perfluoroalkyl;
[0033] (c) chloro- and / or bromo- and / or iodo-C 2 -C 6 fluoroolefins such as chlorotrifluoroethylene (CTFE);
[0034] (d) Perfluoro(alkyl) vinyl ethers such as perfluoro(methyl) vinyl ether (PMVE), perfluoro(ethyl) vinyl ether (PEVE), and perfluoro(propyl) vinyl ether (PPVE);
[0035] (e) Perfluoro(1,3-dioxolene); perfluoro(2,2-dimethyl-1,3-dioxolene) (PDD).
[0036] In a preferred embodiment, polymer (F) is semi-crystalline and contains from 0.1% to 20.0% by mole, preferably from 0.3% to 10.0% by mole, more preferably from 0.5% to 5.0% by mole of repeating units derived from said fluorinated comonomer (CF).
[0037] Polymer (F) can be an elastomer or a semi-crystalline polymer, preferably a semi-crystalline polymer.
[0038] As used herein, the term "semi-crystalline" means a fluoropolymer that also has at least one crystalline melting point in addition to the glass transition temperature Tg in DSC analysis. For the purposes of the present invention, a semi-crystalline fluoropolymer is herein intended to mean a fluoropolymer having a heat of fusion of 10 to 90 J / g, preferably 30 to 80 J / g, more preferably 35 to 75 J / g as measured according to ASTM D3418-08.
[0039] For the purposes of the present invention, the term "elastomer" is intended to designate a true elastomer or a polymer resin used as a base component for obtaining a true elastomer.
[0040] A true elastomer is defined by ASTM, Special Technical Bulletin, Standard No. 184 as a material that can be stretched to twice its natural length at room temperature and, after being held under tension for 5 minutes, once released, will return to within 10% of its initial length in the same amount of time.
[0041] The polymer (F) of the present invention generally has a melting temperature (Tm) included in the range of 100 °C to 200 °C.
[0042] The polymer (F) of the present invention has a quasi-linear structure with a very low degree of branching, which results in substantially negligible insoluble portions due to long branched chains.
[0043] The polymer (F) of the present invention actually preferably has a low fraction of insoluble components in standard polar aprotic solvents (such as NMP) for VDF polymers. More preferably, the solution of polymer (F) in said standard polar aprotic solvent remains homogeneous and stable for several weeks with substantially no insoluble residue.
[0044] Due to the low amount of insoluble components, the GPC and NMR analyses of polymer (F) are not affected, and there are no reliability and reproducibility issues.
[0045] The melting temperature can be determined from the DSC curve obtained by differential scanning calorimetry (hereinafter also referred to as DSC). In the case where the DSC curve shows multiple melting peaks (endothermic peaks), the melting temperature (Tm) is determined based on the peak having the largest peak area.
[0046] It should be understood that parts of different chain ends, defects or other impurity types than those defined above may be included in polymer (F) without impairing its properties.
[0047] According to certain embodiments of the present invention, polymer (F) is characterized by containing end groups having formula (I) as defined above, wherein x is 0.
[0048] According to other embodiments of the present invention, polymer (F) is characterized by containing end groups having formula (I) as defined above, wherein x is 1, and R a is C 2 -C 3 a straight-chain or branched alkyl group, preferably C 3 a straight-chain or branched alkyl group.
[0049] According to other embodiments of the present invention, polymer (F) is characterized by containing end groups having formula (I) as defined above wherein x is 0 and containing end groups having formula (I) wherein x is 1 and R a is C 2 -C 3 a straight-chain or branched alkyl group, preferably C 3 a straight-chain or branched alkyl group.
[0050] Polymer (F) is characterized by having a particle size distribution with a D50 value of less than 240 µm measured by laser diffraction according to ISO 13320.
[0051] D50 designates the particle size at which half of the total is below this value and the other half is above this value.
[0052] The applicant has surprisingly found that polymers (F) having a particle size distribution with a D50 value of less than 240 µm and an intrinsic viscosity in the range of 0.25 l / g to 0.60 l / g, preferably 0.30 l / g to 0.50 l / g, measured in dimethylformamide at 25 °C are particularly suitable for use in electrode-forming compositions having good adhesion to the current collector and optimal slurry viscosity.
[0053] Polymer (F) can be obtained by a method comprising the following steps:
[0054] - Polymerize vinylidene fluoride (VDF) and optionally a comonomer (CF) in an aqueous medium in the presence of a free radical initiator system that introduces a terminal group of formula (I) into the polymer chain.
[0055] - Maintain the pressure in the reactor vessel above the critical pressure of vinylidene fluoride.
[0056] Suitable free radical initiator systems comprise free radical initiators such as bis(ethyl) peroxydicarbonate and hydro-ethyl peroxydicarbonate.
[0057] The amount of free radical initiator required for polymerization depends on its activity and the temperature used for the polymerization. The total amount of free radical initiator used is typically between 100 and 30,000 ppm by weight based on the total weight of the monomers used.
[0058] The free radical initiator can be added in pure form, as a solution, as a suspension or as an emulsion, depending on the initiator selected.
[0059] The free radical initiator system can comprise a chain transfer agent (CTA).
[0060] CTAs suitable for the polymerization process for preparing the polymer (F) according to the invention are those known in the art and are typically selected from the group consisting of short hydrocarbon chains (such as ethane and propane), esters (such as ethyl acetate or diethyl maleate, diethyl carbonate). When using an organic peroxide as an initiator, it can also act as an effective CTA during the free radical polymerization process.
[0061] When used, the CTA can be added all at once at the start of the reaction, or can be added in batches, or continuously throughout the reaction. The amount of CTA and its mode of addition depend on the desired properties of the polymer (F) to be obtained.
[0062] The preferred CTA for use in the process of the invention is diethyl carbonate.
[0063] In the process for preparing the polymer (F), the pressure is maintained above the critical pressure of vinylidene fluoride. Generally, the pressure is maintained at a value greater than 50 bar, preferably greater than 75 bar, even more preferably greater than 100 bar.
[0064] Preferably, the process of the invention is carried out at a temperature above the critical temperature of the VDF monomer (i.e., at least 31 °C).
[0065] The polymer (F) is typically provided in the form of a powder according to the method described above.
[0066] The polymer (F) in powder form can optionally be further extruded to provide the polymer (F) in pellet form.
[0067] The polymer (F) as detailed above can be used as a binder for electrodes in secondary batteries.
[0068] A second object of the present invention relates to an electrode-forming composition (C) comprising:
[0069] a) at least one electrode active material (AM);
[0070] b) at least one binder (B), wherein the binder (B) comprises at least one polymer (F) as defined above; and
[0071] c) at least one solvent (S).
[0072] For the purposes of the present invention, the term "electroactive material (AM)" is intended to denote a compound that is capable of binding or inserting alkali metal or alkaline earth metal ions into its structure during the charging and discharging phases of an electrochemical device and is capable of releasing alkali metal or alkaline earth metal ions therefrom substantially. The compound (AM) preferably is capable of binding or inserting and releasing lithium ions or sodium ions.
[0073] The nature of the compound (AM) in the composition (C) depends on whether the composition is for manufacturing a positive electrode [electrode (Ep)] or a negative electrode [electrode (En)].
[0074] The electrode active material (AM) of the positive electrode is preferably a compound capable of inserting lithium ions or sodium ions.
[0075] Conventional active materials (AM) at the positive electrode of sodium ion batteries are generally selected from Na-based layered transition metal oxides, Prussian blue analogs, and polyanion-type materials.
[0076] In some embodiments, the active material is a Na-based layered transition metal oxide, which is classified as O3-, P2-, and P3-types according to the stacking order of oxygen layers. The P2-type structure generally corresponds to the general formula NaxMO 2 , where M represents transition metal ions such as Co, Mn, and x is 2 / 3.
[0077] In some embodiments, the active material is a Prussian blue analog (PBA) having the general formula A x P[R(CN) 6 1-y □ y .mH 2 O, where A is an alkali metal ion, P is an N-coordinated transition metal ion, R is a C-coordinated transition metal ion, and □ is [R(CN) 6 Vacancy, where 0 ≤ x ≤ 2 and 0 ≤ y < 1, such as Na 0.81 Fe[Fe(CN) 6 0.79 □ 0.21 、NaFe 2 (CN) 6 、Na1 .63 Fe 1.89 (CN) 6 、Na 1.72 MnFe(CN) 6 、Na 1.76 Ni 0.12 Mn 0.88 [Fe(CN) 6 0.98 、Na 2 Ni x Co 1-x Fe(CN) 6 (where 0 ≤ x ≤ 1, for example Na 2 CoFe(CN) 6 ).
[0078] In some other embodiments, the active material is a polyanion-type material having the general formula Na x M y (XO 4 ) n (where X = S, P, Si, As, Mo, and W, and M is a transition metal), and these materials have a series of tetrahedral anion units (XO 4 ) n- and their derivatives (X m O 3m+1 ) n- . Among them, phosphates NaMPO 4 such as NaFePO 4 、Na 0.7 FePO 4 or NaMnPO 4 ; sodium (natrium / sodium) superionic conductors of NASICON-type structure having the general formula Na x M 2 (XO 4 ) 3 (where 1 ≤ x ≤ 4, and M = V, Fe, Ni, Mn, Ti, Cr, Zr...; X = P, S, Si, Se, Mo...), single-transition metal types such as Na 3 V 2 (PO 4 ) 3 (NVP), Na 3 Cr 2 (PO4 ) 3 、Na 3 Fe 2 (PO 4 ) 3 ; – Binary transition metal types such as Na 2 VTi(PO 4 ) 3 、Na 3 FeV(PO 4 ) 3 、Na 4 MnV(PO 4 ) 3 、Na 3 MnZr(PO 4 ) 3 、Na 3 MnTi(PO 4 ) 3 、Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 )(NFPP); Pyrophosphate Na 2 FeP 2 O 7 、Na 2 MnP 2 O 7 、Na 2 CoP 2 O 7 、Na 4-x Fe 2+x / 2 (P 2 O 7 ) 2 (where 2 / 3 ≤ x ≤ 7 / 8, for example Na 3.12 Fe 2.44 (P 2 O 7 ) 2 or Na 3.32 Fe 2.34 (P 2 O 7 ) 2 )、Na 2 (VO)P 2 O 7 、Na 7 V 3 (P 2 O 7 ) 4 ; Fluorophosphate NaVPO 4 F、Na 2 CoPO 4 F、Na2 FePO 4 F, Na 2 MnPO 4 F, Na 3 (VO 1-x PO 4 ) 2 F 1+2x (where 0 ≤ x ≤ 1, e.g., Na 3 (VOPO 4 ) 2 F or Na 3 V 2 (PO 4 ) 2 F 3 (NVPF)); Fluorosulfates, such as NaMSO 4 F (where M = Fe, Co, Ni); Having the general formula Na 4 M 3 (PO 4 ) 2 (P 2 O 7 )(where M represents a transition metal) Mixed phosphates / pyrophosphates, such as Na 4 Mn 3 (PO 4 ) 2 (P 2 O 7 )、Na 4 Co 3 (PO 4 ) 2 (P 2 O 7 )、Na 4 Ni 3 (PO 4 ) 2 (P 2 O 7 )、Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 )(NFPP)、Na 7 V 4 (P 2 O 7 ) 4 (PO 4 );Sulfates, such as Na 2 Fe 2 (SO 4 ) 3 、Na 2+ 2x Fe2-x (SO 4 ) 3 、Na 2+2x Co 2-x (SO 4 ) 3 、Na 2+2x Mn 2-x (SO 4 ) 3 (where 0 ≤ x ≤ 1); silicates having the general formula Na 2 MSiO 4 (where M = Mn, Fe, Co, and Ni).
[0079] In some preferred embodiments, the active material is preferably a fluorophosphate selected from the list consisting of: NaVPO 4 F, Na 2 CoPO 4 F, Na 2 FePO 4 F, Na 2 MnPO 4 F, Na 3 (VO 1-x PO 4 ) 2 F 1+2x (where 0 ≤ x ≤ 1, e.g., Na 3 (VOPO 4 ) 2 F or Na 3 V 2 (PO 4 ) 2 F 3 (NVPF)).
[0080] Conventional active materials (AMs) at the positive electrode of a lithium-ion battery can include composite metal chalcogenides having the formula LiMQ 2 , where M is at least one metal selected from transition metals such as Co, Ni, Fe, Mn, Cr, and V and Q is a chalcogen element such as O or S. Among these, lithium-based composite metal oxides having the formula LiMO 2 are preferably used, where M is the same as defined above. Preferred examples thereof can include LiCoO 2 , LiNiO 2 , LiNi x Co 1-x O 2 (0 < x < 1), and spinel-structured LiMn 2 O 4 .
[0081] Alternatively, the electrode active material can comprise an electroactive material based on lithiated or partially lithiated transition metal oxyanions having the formula M 1 M 2 (JO 4 ) f E 1-f , where M 1 is lithium, which can be partially replaced by another alkali metal that accounts for less than 20% of M 1 metal; M 2 is a transition metal selected from Fe, Mn, Ni or mixtures thereof at an oxidation level of +2, which can be partially replaced by one or more additional metals that are at an oxidation level between +1 and +5 and account for less than 35% of M 2 metal, including 0; JO 4 is any oxyanion, where J is P, S, V, Si, Nb, Mo or a combination thereof; E is a fluoride anion, a hydroxide anion or a chloride anion; f is the mole fraction of the JO 4 oxyanion, typically included between 0.75 and 1.
[0082] M as defined above 1 M 2 (JO 4 ) f E 1-f The electroactive material is preferably phosphate-based and can have an ordered or modified olivine structure.
[0083] More preferably, the electrode active material has the formula Li 3-x M’ y M” 2-y (JO 4 ) 3 , where 0 ≤ x ≤ 3, 0 ≤ y ≤ 2, M’ and M” are the same or different metals, at least one of which is a transition metal, and JO 4 is preferably PO 4 , which can be partially replaced by another oxyanion, where J is S, V, Si, Nb, Mo or a combination thereof. Even more preferably, the electrode active material (AM) is a phosphate-based electroactive material having the following formula
[0084] Li x A y D z PO 4 ,
[0085] where A is selected from the group consisting of Mn, Fe, Co, Ni and Cu; D is selected from the group consisting of Mg, Ca, Sr, Ba; and x, y and z are numbers satisfying the following relationships: 0 < x < 2, 0 < y < 1.5, 0 ≦ z < 1.5.
[0086] Component A is preferably Fe, Mn, and Ni, and particularly preferably Fe.
[0087] Component D is preferably Mg or Ca.
[0088] Examples of compounds having an olivine structure include lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), and lithium manganese phosphate.
[0089] In addition, as the positive electrode active material (AM), a material whose surface is partially or entirely covered with carbon can be used to supplement conductivity.
[0090] Based on 100 parts by weight of the positive electrode active material, the amount of the coated carbon is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and still more preferably 5 parts by weight or less.
[0091] Relative to the entire positive electrode active material (AM) at 100% by mass, the compound having an olivine structure is present in the composition (C) in an amount of 70% by mass or more.
[0092] More preferably, the amount is 90% by mass or more, and most preferably, the positive electrode active material (AM) consists only of the compound having an olivine structure.
[0093] Most preferably, the positive electrode active material (AM) consists only of lithium iron phosphate (LFP).
[0094] In the positive electrode composition of the present invention, the active material (AM) has an average particle size of 3 μm or less.
[0095] The average particle size (D50) of the compound having an olivine structure is more preferably in the range of 0.01 to 1.8 μm.
[0096] The average particle size of the positive electrode active material can be measured by a particle size distribution meter for dynamic light scattering.
[0097] As the average particle size becomes smaller, the surface area becomes larger and the binder must bond with a small amount of binder, so the binder is required to have flexibility.
[0098] By using a positive electrode active material containing a compound having an olivine structure with an average particle size of 3 μm or less, the electrical characteristics (such as output characteristics) when the positive electrode composition of the secondary battery is used as the positive electrode of the battery are excellent.
[0099] In the case of forming a composite negative electrode (En) for a secondary battery, the compound (AM) may preferably contain a carbon-based material and / or a silicon-based material.
[0100] In some embodiments, the carbon-based material can be, for example, graphite (such as natural or artificial graphite), graphene, or carbon black.
[0101] These materials can be used alone or in a mixture of two or more of them.
[0102] The carbon-based material is preferably graphite.
[0103] The silicon-based compound can be one or more selected from the group consisting of: chlorosilane, alkoxysilane, aminosilane, fluoroalkylsilane, silicon, silicon chloride, silicon carbide, and silicon oxide. More particularly, the silicon-based compound can be silicon oxide or silicon carbide.
[0104] When present in the compound (AM), at least one silicon-based compound is included in the compound (AM) in an amount in the range of 1% to 30% by weight, preferably 5% to 20% by weight, based on the total weight of the compound (AM).
[0105] The solvent (S) can preferably be an organic polar solvent, examples of which can include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, and trimethyl phosphate. These solvents can be used alone or in a mixture of two or more substances.
[0106] An optional conductive agent can be added to improve the conductivity of the resulting electrode (AM).
[0107] Examples of which can include: carbonaceous materials such as carbon black, fine graphite powder, carbon nanotubes, graphene, or fibers, or fine powders or fibers of metals such as nickel or aluminum. The optional conductive agent is preferably carbon black. Carbon black is, for example, available under the trade name Super or obtainable.
[0108] The electrode-forming composition (C) of the present invention can further optionally contain at least one conductive agent.
[0109] When present, the conductive agent is different from the carbon-based material described above.
[0110] In a preferred embodiment of the present invention, there is provided an electrode-forming composition (C) for use in the preparation of a positive electrode (Ep), the composition comprising:
[0111] a) at least one positive electrode active material (AM);
[0112] b) at least one binder (B), wherein the binder (B) contains at least one polymer (F) as defined above;
[0113] c) at least one solvent (S); and
[0114] d) at least one electrically conductive agent, preferably selected from carbon black, fine graphite powder, or carbon nanotubes.
[0115] As described above, the polymer (F) of the present invention has a quasi-linear structure and, when dissolved in a standard polar aprotic solvent (such as NMP), the amount of the insoluble portion is very low.
[0116] Due to the low amount of the insoluble component, the polymer (F) provides a solution in an organic solvent that is not adversely affected by the presence of insoluble residues, which are commonly referred to as "gels", and is thus more suitable for formulating an electrode-forming composition.
[0117] In another object, the present invention relates to the use of an electrode-forming composition (C) for manufacturing an electrode (E), the method comprising:
[0118] (I) providing a metal substrate having at least one surface;
[0119] (II) providing the electrode-forming composition (C) as defined above;
[0120] (III) applying the composition (C) provided in step (II) to the at least one surface of the metal substrate provided in step (I), thereby providing an assembly comprising a metal substrate coated with the composition (C) on the at least one surface;
[0121] (IV) drying the assembly provided in step (III);
[0122] (V) subjecting the dried assembly obtained in step (IV) to a compression step to obtain the electrode (E) of the present invention.
[0123] In a further object, the present invention relates to an electrode (E) obtainable by the method of the present invention.
[0124] The applicant has unexpectedly found that the electrode (E) of the present invention exhibits excellent adhesion of the binder to the current collector.
[0125] The electrode (E) of the present invention is thus particularly suitable for use in electrochemical devices, especially secondary batteries.
[0126] For the purposes of the present invention, the term "secondary battery" is intended to denote a rechargeable battery.
[0127] The secondary battery of the present invention is preferably an alkali metal or alkaline earth metal secondary battery.
[0128] The secondary battery of the present invention is more preferably a sodium ion or lithium ion secondary battery.
[0129] For yet additional purposes, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention.
[0130] The electrochemical device according to the present invention (preferably a secondary battery) comprises:
[0131] - a positive electrode and a negative electrode,
[0132] wherein at least one of the positive electrode and the negative electrode is the electrode (E) of the present invention.
[0133] In a preferred embodiment of the present invention, there is provided an electrochemical device as a secondary battery, which comprises:
[0134] - a positive electrode and a negative electrode,
[0135] wherein the negative electrode is the electrode (E) according to the present invention.
[0136] The electrochemical device according to the present invention can be prepared by standard methods known to those skilled in the art.
[0137] If the disclosure content of any patent, patent application, and publication incorporated herein by reference conflicts with the description of the present application to the extent that it may cause the terms to be unclear, then the present specification shall prevail.
[0138] The present invention will now be described with reference to the following examples, which are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0139] Experimental Section
[0140] Determination of the Intrinsic Viscosity of Polymer (F)
[0141] The intrinsic viscosity (η) [dl / g] was measured using the following equation based on the falling time of a solution at a concentration of about 0.2 g / dl obtained by dissolving polymer (F) in N,N-dimethylformamide at 25 °C using an Ubbelhode viscometer:
[0142]
[0143] where c is the polymer concentration [g / dl], η r is the relative viscosity, i.e., the ratio between the falling time of the sample solution and the falling time of the solvent, η sp is the specific viscosity, i.e., η r - 1, and Γ is the experimental factor, which corresponds to 3 for polymer (F).
[0144] DSC Analysis
[0145] DSC analysis was carried out according to ASTM D 3418 standard; the melting point (T f2 ) was determined at a heating rate of 10 °C / min.
[0146] Determination of polar end groups
[0147] The amount of polar end groups of polymer (F) generated from the ethyl chloroformate initiator precursor used in the polymerization process was determined by 1 1H-NMR, measuring the intensity of the H atom of the CH 2 group (shown in bold in the following formula) relative to the total intensity of the CH2 moiety of the VDF monomer unit of the polymer (F) backbone:
[0148] CH 3 -CH 2 -OCOO-CH 2 -CF 2 -
[0149] The content of the end groups was calculated by applying the following formula:
[0150] [EG] = (I EG / I VDF ) × 10000
[0151] where:
[0152] -[EG] is the content of the general end group, expressed as moles / 10000 VDF units,
[0153] -I EG is the integrated intensity of the end group [EG], normalized to one hydrogen,
[0154] -I VDF is the integrated intensity of the normal and reverse VDF repeat units, normalized to one hydrogen.
[0155] Approximately 20 mg of the polymer was dissolved in 0.7 ml of deuterated acetone. The 1 1H-NMR spectrum recorded at 60 °C showed the above-mentioned CH 2 at 4.47 ppm, while the CH 2 signals from the normal and reverse VDF repeat units resonated as broad peaks centered at 2.93 ppm and 2.36 ppm, respectively.
[0156] As known to those skilled in the art, a similar NMR method was applied to determine the end groups (CH 3 -CH 2 -OCOO-CH 2 -CH 2 -, CH 3 -CH2 -OCOO-CH(CH 3 )-) and for determining –CF 2 H and -CF 2 CH 3 end groups.
[0157] Example 1: Preparation of Polymer F-1
[0158] In a 4 L reactor equipped with an impeller operating at 650 rpm, the following components were introduced sequentially: demineralized water at 2376 g per kg of total monomers and 0.4 g of PEO (from Alroko ), and 0.5 g of hydroxypropyl methylcellulose per kg of total monomers (from Dow ), and 12.4 g of trisodium phosphate. At a fixed temperature of 14 °C, the oxygen present in the reactor was removed by sequential vacuum and nitrogen purges. This sequence was repeated 3 times.
[0159] Then, 10.16 g of hydrogen peroxide solution (from Brenntag) and 3.53 g of ethyl chloroformate (from Framochem) and 1.76 g of diethyl carbonate were introduced into the reactor.
[0160] After 15 minutes at a stirring speed of 880 rpm, 1176 g of VDF was introduced into the reactor. Then, the reactor was gradually heated until the set point temperature of 35 °C was reached.
[0161] During the entire polymerization run, the pressure was kept constantly equal to 120 bar by feed water. A total of 657 g of water was charged into the reactor. After 162 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached.
[0162] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After the washing process, the polymer was dried overnight in an oven at 65 °C. 882 g of dry powder was collected.
[0163] A polymer was obtained with an intrinsic viscosity of 0.316 l / g in DMF at 25 °C and a T 2 f of 172.1 °C.
[0164] The polymer contained end groups CH 3 CH 2 -OCOO-: 0.7 / 10000 VDF units derived from the ethyl chloroformate initiator precursor and 1.0 / 10000 VDF units derived from diethyl carbonate.
[0165] In addition, the -CF of the 2.3 / 10000 VDF unit was determined 2 H and the -CF of the 1.4 / 10000 VDF unit 2 CH 3 The presence of end groups.
[0166] Example 2: Preparation of Polymer F-2
[0167] In an 80 l reactor equipped with an impeller operating at 250 rpm, the following components were introduced sequentially: 52.4 Kg of demineralized water and 0.4 g of hydroxypropyl methylcellulose (from Dow Chemical Company ) per Kg of VDF. At a fixed temperature of 20 °C, the oxygen present in the reactor was removed by sequential vacuum and nitrogen purges. This sequence was repeated 3 times.
[0168] Then, a solution (75%) of 41.38 g of the initiator tert-amyl perneodecanoate (from United Initiators) in isododecane and 250.02 g of diethyl carbonate were introduced into the reactor. Subsequently, the stirring speed was immediately increased to 300 rpm, and 22.99 Kg of VDF was added to the reactor. Then, the reactor was gradually heated until the set point temperature of 52 °C was reached. During the entire polymerization run, the pressure was kept constantly equal to 120 bar by VDF. A total of 11.49 Kg of VDF was charged, and no more VDF was charged. Then the temperature was raised to 65 °C, and then after a total of 169 minutes, the reaction was stopped by degassing the suspension until atmospheric pressure was reached.
[0169] Then the polymer was collected by filtration and suspended in clean water in a stirred tank. After the washing treatment, the polymer was dried overnight in an oven at 65 °C. 29.94 Kg of dry powder was collected.
[0170] Polymer A: A VDF homopolymer having an intrinsic viscosity of 0.271 l / g in DMF at 25 °C and a T 2 f of 170.2 °C.
[0171] This polymer contains end groups CH 3 CH 2 -OCOO derived from diethyl carbonate for 2.2 / 10000 VDF units, -C(CH 3 ) 3 from the initiator for 0.6 / 10000 VDF units, -CF 2 H for 4.5 / 10000 VDF units, and -CF 2 CH 3 end groups for 2.4 / 10000 VDF units.
[0172] General Preparation of Electrodes with NMC811 Active Material
[0173] The following is the preparation of a positive electrode with a final composition of 98% by weight of NMC811 (Cosmo Advanced Materials & Technology, d50 = 10.28 μm), 1.1% by weight of polymer, and 0.9% by weight of conductive additive.
[0174] The slurry components were added to a mixing cup in the following order: 33.6 g of a multi-walled carbon nanotube dispersion with a solid content of 4.1% by weight, 21.1 g of an 8% by weight polymer solution in NMP, 150 g of NMC, and 7.9 g of NMP.
[0175] Then the mixture was mixed for 5 minutes at 500 rpm using a high-speed disk impeller and then for 75 minutes at 1900 rpm.
[0176] The positive electrode was obtained by casting the dispersion thus obtained onto a 15-μm-thick aluminum foil using a doctor blade and drying the so-coated layer in a vacuum oven at a temperature of 90 °C for about 50 minutes. The thickness of the dried coating was about 150 μm.
[0177] Example 3: Adhesion and Slurry Viscosity
[0178] The polymers of Example 1 and Example 2 have been used as binders and electrode compositions have been produced according to the procedures shown above.
[0179] The slurry viscosity of the composition as defined above was measured using an Anton Paar Rheolab QC with a concentric cylinder device (Measuring cup: C-CC27 / QC-LTD Bob: CC27 / P6) at 25 °C under Peltier temperature control. The steady-state viscosity was measured at shear rates from 0.1 to 1000 1 / s.
[0180] The adhesion peel force between the aluminum foil and the electrode was measured as follows:
[0181] A 180° peel test was carried out at 20 °C at a speed of 300 mm / min according to the setup described in Standard ASTM D903 to evaluate the adhesion of the dried coating to the aluminum foil as defined above.
[0182] The values of slurry viscosity and adhesion are shown in Table 1.
[0183] Table 1
[0184]
[0185] General Preparation of Electrodes with LFP Active Material
[0186] A positive electrode with a final composition of 95.75% by weight of LFP (Phostech Lithium, d50 = 0.5 μm), 3.5% by weight of polymer, and 0.75% by weight of conductive additive was prepared as follows.
[0187] A first dispersion was prepared by premixing 34.3 g of an 8% by weight polymer solution in NMP, 75.07 g of LFP, 14.7 g of graphite fine powder carbon nanotubes pre-dispersed in NMP at 4% by weight, and 15.93 g of NMP in a centrifugal mixer for 10 minutes.
[0188] Then the mixture was mixed at 1500 rpm for 50 minutes using a high-speed butterfly impeller. Subsequently, an additional 5.2 g of NMP was added to the dispersion, and it was further mixed in the centrifugal mixer for 5 min. The positive electrode was obtained by casting the thus-obtained combined stream onto a 15-μm thick Al foil using a spatula and drying the so-coated layer in a vacuum oven at a temperature of 90 °C for about 50 minutes. The thickness of the dried coating was about 100 μm.
[0189] Example 4: Adhesion and Slurry Viscosity
[0190] The polymers of Example 1 and Example 2 were used as binders and electrode compositions were produced according to the procedures shown above. The values of slurry viscosity and adhesion measured as defined above are shown in Table 2.
[0191] Table 2
[0192]
[0193] It is known to those skilled in the art that the adhesion value of the binder to the current collector is largely affected by the particle size of the active material used to prepare the electrode; thus, when the percentage amount of the active material in the electrode is the same, using active materials with different particle sizes has a significant impact on the adhesion value.
[0194] Independent of the above, the results in Table 1 and Table 2 show that the polymers of the present invention have good performance, resulting in good adhesion to the current collector.
Claims
1. A VDF-based polymer [polymer (F)] consisting of repeating units derived from VDF and optionally containing repeating units derived from at least one fluorinated comonomer (CF) different from VDF, the polymer (F) having an intrinsic viscosity measured in dimethylformamide at 25 °C in the range of 0.25 l / g to 0.60 l / g, preferably 0.30 l / g to 0.50 l / g, as determined by the method reported in the specification. wherein the polymer (F) is characterized by containing end groups having the formula (I): –(R a ) x -O-CO-O-CH 2 -CH 3 (I) wherein R a is C 1 -C 5 a straight-chain or branched-chain hydrocarbon group, and x is an integer selected from 1 and 0, and These end groups having the formula (I) are present in an amount of at least 0.2 / 10000 VDF units, preferably at least 1.0 / 10000 VDF units, and at most 10 / 10000 VDF units, as determined by the method reported in the specification. The polymer (F) is characterized by having a particle size distribution with a D50 value of less than 240 microns measured by laser diffraction according to ISO 13320.
2. The polymer (F) according to claim 1, which is a VDF homopolymer.
3. The polymer (F) according to claim 1, which is a VDF-based copolymer comprising repeating units derived from VDF and repeating units derived from at least one fluorinated comonomer (CF) different from VDF.
4. The polymer (F) according to any one of claims 1 to 3, wherein, the fluorinated comonomer (CF) is selected from the group consisting of: (a) C 2 -C 8 Fluoroolefins and / or perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene, hexafluoroisobutene, vinyl fluoride; 1,2-difluoroethylene and trifluoroethylene; (b) having the formula CH 2 =CH-R f0 wherein R f0 is C 1 -C 6 perfluoroalkyl; (c) chloro- and / or bromo- and / or iodo-C 2 -C 6 fluoroolefins, such as chlorotrifluoroethylene (CTFE); (d) perfluoro(alkyl) vinyl ethers such as perfluoro(methyl) vinyl ether (PMVE), perfluoro(ethyl) vinyl ether (PEVE), and perfluoro(propyl) vinyl ether (PPVE); (e) perfluoro(1,3-dioxolene); perfluoro(2,2-dimethyl-1,3-dioxolene) (PDD).
5. The polymer (F) according to claim 4, wherein, the polymer (F) contains repeating units derived from the fluorinated comonomer (CF) in an amount of 0.1% to 20.0% by mole, preferably 0.3% to 10.0% by mole, more preferably 0.5% to 5.0% by mole.
6. The polymer (F) according to any one of the preceding claims, which contains end groups of formula (I) in which x is 0, and / or end groups of formula (I) in which x is 1 and R a is C 2 -C 3 is a linear or branched alkyl group.
7. A method for preparing the polymer (F) according to any one of claims 1 to 6, the method comprising: - polymerizing vinylidene fluoride (VDF) monomer, and optionally a comonomer (CF), in an aqueous medium in the presence of a free radical initiator system which introduces a terminal group of formula (I) into the polymer chain, and - maintaining the pressure in the reactor vessel above the critical pressure of the vinylidene fluoride.
8. The method according to claim 7, wherein, the free radical initiator system contains a free radical initiator such as bis(ethyl) peroxydicarbonate and ethyl peroxycarbonate.
9. The method according to claim 8, wherein, the free radical initiator system contains a chain transfer agent (CTA).
10. An electrode forming composition (C) comprising: a) at least one electrode active material (AM); b) at least one binder (B), wherein the binder (B) contains at least one polymer (F) according to any one of claims 1 to 6; and c) at least one solvent (S).
11. The electrode forming composition (C) according to claim 10, wherein, The at least one electrode active material (AM) is LFP.
12. A method for manufacturing an electrode [electrode (E)], the method comprising: (I) providing a metallic substrate having at least one surface; (II) providing an electrode-forming composition (C) according to claim 10 or claim 11; (III) applying the composition (C) provided in step (II) to the at least one surface of the metallic substrate provided in step (I), thereby providing an assembly comprising a metallic substrate having the composition (C) coated on the at least one surface; (IV) drying the assembly provided in step (III); (V) subjecting the dried assembly obtained in step (IV) to a compression step to obtain the electrode (E) of the present invention.
13. An electrode (E) obtainable by the method according to claim 12.
14. An electrochemical device comprising at least one electrode (E) according to claim 13.